Development, Performance and Emission Assessment of a Single-cylinder Air-cooled Gasoline Crank-Rocker Engine - HASSAN, SALAH ELDIN MOHAMMED ELFAKKI (2018)
Improving internal combustion engine performance and reducing exhaust emission is a main concern for engine manufacturers nowadays